Impact of Aggressive Communication Styles of School Heads on Teachers’ Emotional Stress at Secondary Schools in Bannu District: https://doi.org/10.5281/zenodo.17406153 - Rifat Ullah; Dr. Rahmat Ullah Shah; Dr. Asif Ali Khan (Journal of Religion and Society, 2025)
The purpose of this study was; to investigate Communication Styles of School Heads and Their Influence on Teachers’ Emotional Stress at secondary level in Bannu District. The study was descriptive in nature so descriptive survey design was used by the researcher to conduct the study. The study was descriptive in nature so descriptive survey design was used by the researcher to conduct the study. All 130 (Male/Female) secondary schools and all 1627(Male/Female) secondary schools’ teachers working in secondary schools of Bannu district was the population of the study. Stratified random sampling technique was used to draw sample for the study. The sample size was justified by using Krejice& Morgan (1970) formula. The sample of the study was comprised of 56 secondary schools and 327 secondary school male and female teachers working in secondary schools in Bannu District. Two Questionnairess for the teachers were used to collect data from the sampled respondents. The collected data was analyzed by using Mean, Standard deviation. Regression used to find out required findings and conclusions. The study found that school heads commonly used average levels of both passive and aggressive communication styles, which significantly contributed to emotional stress among secondary school teachers. Regression analysis confirmed a notable statistical relationship between these communication behaviors and teacher well-being, leading to the rejection of the null hypothesis. Aggressive communication had a slightly stronger impact, though both styles proved detrimental. In light of these findings, it is recommended that school systems prioritize the enhancement of leadership communication through targeted training, feedback mechanisms, and policy reforms. Key Words: Schools Heads, Aggressive Communication Styles, Teachers’ Emotional Stress at Secondary level, Bannu